The hospitality of communication in Islam: an analytical study on contemporary works of tafsīr - Wahyono, Zubaidi; Jani, Mohd. Shah; Solihin, Sohirin Mohammad (IIUM Press, 2019)
The paper attempts to elucidate different levels of hospitality that relates to human communication. It focuses mainly on reading verses of the Qurʾān that speak of ethical conduct in dealing with others and analysing its contexts. The divine message given to the Prophet Muhammad PBUH emphasises on the significance of hospitable relation in every sphere of human life. It plays extremely important role in avoiding misunderstanding and conflict within the society. The emergence of tensions between individuals in the community has always been the result of harshness and negative words applied in communication. In the discussion, we employ the method of deductive analysis on the views of contemporary scholars in the field of Qurʾanic tafsīr who interpret the verses adopting a sort of contextual approach. The scope of the study is limited to analysing the interpretation of verses related to ethical relation between individuals, family members, diverse religious adherents, and governmental leaders. The significance of this study is that it addresses the question of why humanity should take benefit from the Qurʾanic guidance on the hospitality of communication to maintain peace and harmonious life.